First you pick one of the equations and solve for one of the variables. You can pick either equation. Let's pick the first equation and solve for b:
First we subtract 6 from both sides: 7a-6=-b
Next we multiply both sides by -1 in order to get the value of b: -7a+6=b
Now that we have solved for b in the first equation, we plug the value of b into the second equation:
On the right hand side of the equation, we distribute the negative into the parenthesis: 7a=4+7a-6
Then to get the a's on the same side, we subtract 7a from both sides: 0=4-6
Simplifying the right hand side we get 0=-2. Since this is a false statement, then our method of substitution has shown us that the answer is (c) There are no solutions.